Pemberdayaan Kelompok Wanita Berdikari Tanjung Lom Dalam Hilirisasi Tepung Pisang Berbasis Ekonomi Hijau - Rate, Suherman; Dewanti, Ritma; Herman, Hernianti; Dahro, Ahmad; Hadi, Anto J; Ishak, Syamsopyan (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Downstreaming of local food ingredients such as bananas is still not widely encouraged, even though bananas are a fruit rich in vitamins and minerals. Based on interviews with partners conducted by the STIKES Adila service team, it is known that the local potential of Tanjung Agung village has not been utilized optimally due to a lack of knowledge. Because of this, community service is carried out in making banana flour and downstreaming processed banana flour products. Implementing this community service is training in making banana flour and downstream products from banana flour. Based on the results of community service activities, the Tanjung Lom Independent Women group experienced increased knowledge and skills in making banana flour and processed products using banana flour. The output obtained from this community service activity is that the participants can have the skills to make banana flour. The follow-up to this activity is that the Women's group develops skills which are the basis for the formation of Micro, Small and Medium Enterprises thereby improving the economy in Tanjung Agung Village.